Detection and Analysis of Packet Sniffing Attacks Using Wireshark on Wifi Networks: A Practical Approach to Network Security Case Study of Puskesmas Sungsang - M. Hajaji Alfarizi; Zulhipni Reno Saputra Elsi; Apriansyah; Karnadi4 (Universitas Islam Kuantan Singingi, 2025)
In the last two decades, advances in internet technology have significantly influenced various sectors, including healthcare. The integration of information technology into health services has become essential for improving operational efficiency through integrated medical information systems, structured patient management, and digital financial administration. The Sungsang Health Center, as a community-based healthcare facility, relies heavily on networked systems to support daily activities such as patient registration and electronic medical record management, which involve highly sensitive data. This condition increases the risk of data leakage, particularly due to packet sniffing attacks. Therefore, strengthening network security policies is a critical need. This research aims to analyze potential packet sniffing threats and support the prevention of data leaks at the Sungsang Health Center by utilizing Wireshark as a network analysis tool. Wireshark enables detailed monitoring and analysis of data packets to identify suspicious activities that are not easily detected manually. The study provides insights into techniques for detecting and analyzing network vulnerabilities, which can serve as a reference for improving network security policies. The results are expected to support the development of safer and more reliable digital health systems and raise awareness of the importance of protecting patient data.